Angiosarcoma in the chest: radiologic–pathologic correlation. Issue 48 (November 2016) - Piciucchi, Sara; Dubini, Alessandra; Tomassetti, Sara; Sanna, Stefano; Ravaglia, Claudia; Carloni, Angelo; Gurioli, Christian; Gurioli, Carlo; Colby, Thomas V.; Poletti, Venerino
Abstract: Rationale: Angiosarcomas are rare, malignant vascular tumors. Patient concerns: They represents about 2% of all soft tissue sarcoma, which can often metastasize through the hematogenous route. The radiological features have been analyzed in 4 patients with metastatic angiosarcoma in the chest. Diagnoses: The main radiologic findings included nodules, cysts, nodules with halo sign, and vascular tree-in-bud. Morphologic features, as observed in the histologic specimen, have been correlated with radiologic appearance. Lessons: Metastatic angiosarcomas to the lung are characterized by a wide variety of radiologic appearances that can be very characteristic. Computed tomographic findings observed include bilateral solid nodules, cystic, and bullous lesions sometimes associated with spontaneous hemopneumothoraces.